Battery-grade lithium carbonate and preparation method thereof

Through the evaporation and concentration of high sulfur salt precipitation lithium mother liquor and adsorption of homemade chelating resin, combined with the cyclic shear and water washing of the intelligent cutting and sharp grinding system, the problems of medium and high cost and high energy consumption of battery-grade lithium carbonate preparation are solved, and high purity is achieved And low-impact battery-grade lithium carbonate preparation, meeting environmental protection requirements.

CN119240757APending Publication Date: 2025-01-03CHONGQING HUAN LITHIUM RECYCLING TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411380409.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art faces the problems of high production costs and high energy consumption when preparing battery-grade lithium carbonate. The traditional carbonization purification method is not environmentally friendly, the industrial-grade lithium carbonate conversion efficiency is low, and it is difficult to effectively control the impurity content.

Method used

The high sulfur salt precipitation lithium mother liquor was evaporated and concentrated, and the calcium and magnesium ions in the filtrate were adsorbed by homemade chelating resin. The circulating shearing and two-stage washing was performed through intelligent cutting and sharp grinding system to obtain battery-grade lithium carbonate with a purity of more than 99.6%. .

Benefits of technology

It reduces the production cost of battery-grade lithium carbonate, improves product purity, reduces equipment requirements, and complies with the requirements of carbon neutrality policy, and the impurity content is lower than the standard limit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240757A_ABST
    Figure CN119240757A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium carbonate, and relates to battery-grade lithium carbonate and a preparation method thereof.The preparation method comprises the following steps that S1, lithium precipitation mother liquor is decarburized, and after decarburization, the lithium precipitation mother liquor is sequentially evaporated, concentrated and filtered to obtain concentrated liquor; s2, preparing a chelating resin for removing calcium and magnesium in a high sodium sulfate salt environment; s3, enabling the concentrated solution to pass through chelating resin to obtain a calcium and magnesium removed concentrated solution; s4, performing lithium precipitation on the sodium carbonate solution and the concentrated solution to obtain lithium carbonate slurry, and pumping the lithium carbonate slurry into an intelligent cutting sharpening system for circular shearing; and S5, lithium carbonate is filtered out after cyclic shearing, then two-stage washing is conducted, and secondary cyclic shearing is conducted through an intelligent cutting sharpening system in the second-stage washing process. According to the method disclosed by the invention, a traditional carbonization purification process is abandoned, a two-time cyclic shearing method is utilized, peritectic is opened for a traditional lithium precipitation system, preservation residues are solved, the content of sodium and sulfate radicals is effectively reduced, and a battery-grade lithium carbonate product is finally obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium carbonate and relates to battery-grade lithium carbonate and a preparation method thereof. Background Art

[0002] Lithium is a metal element in the second period IA group of the periodic table. The most common valence is +1, and it usually only appears in the form of +1 ions in aqueous solution. Lithium carbonate is a basic compound of lithium and has a variety of industrial uses. It is widely used as a basic raw material in industries such as batteries, ceramics, glass, medicine, refrigeration, and new energy storage. It has two forms: amorphous white powder and prismatic colorless monoclinic crystals. The national industry standard divides lithium carbonate into industrial-grade lithium carbonate, battery-grade lithium carbonate, and high-purity lithium carbonate. Battery-grade lithium carbonate is a key raw material for the production of lithium-ion battery positive electrode materials and electrolyte additives such as LiCoO2, LiFePO4, and LiMn2O4. At present, the main production methods of battery-grade lithium carbonate include lithium extraction from salt lake brine, lithium extraction from lithium ore, and lithium extraction from waste lithium batteries. With the rapid increase in the demand for lithium-ion batteries in industries such as electronics and new energy vehicles, the demand for battery-grade lithium carbonate is increasing, and the quality requirements are also getting higher and higher. Therefore, it is necessary to further study the preparation process technology of battery-grade lithium carbonate.

[0003] Due to different sources, even if the lithium salt composition meets the minimum standard, the fluctuation of various impurity contents will still affect the quality of the final product because the source of lithium salt of the user unit cannot be guaranteed to be uniform. At present, in order to obtain battery-grade lithium carbonate, facing the lithium extracted from salt lake brine, the lithium salt from this source usually contains more impurities such as magnesium, boron, chlorine, etc., or the lithium produced when recycling waste lithium batteries, the lithium salt from this source usually contains more impurities such as sodium, calcium, magnesium, sulfate, etc., although carbonization purification is the most effective method for purifying lithium carbonate, it also faces problems such as high production cost and strict equipment requirements.

[0004] Patent 202311220548.2 discloses a method for preparing battery-grade lithium carbonate, wherein a sodium carbonate solution is added to a pre-configured lithium sulfate solution to generate a sodium sulfate solution containing a crude lithium carbonate precipitate, and then the sodium sulfate solution is subjected to solid-liquid separation to obtain a solid phase crude lithium carbonate precipitate, and the separated solid phase crude lithium carbonate precipitate is mixed and stirred with water to obtain a slurry, and the slurry is purified by high-purity carbon dioxide to obtain a lithium carbonate solution, and the lithium carbonate solution is subjected to solid-liquid separation to obtain battery-grade lithium carbonate. However, this method is a relatively traditional carbonization purification method, which requires a large investment in equipment costs, and the whole process has high energy consumption, which is not an economical and efficient purification method.

[0005] Patent CN201310507395.X discloses a method for preparing battery-grade lithium carbonate using industrial-grade lithium carbonate, which mainly includes carbonizing industrial-grade lithium carbonate and distilled water, removing impurities such as calcium and magnesium with ion exchange resin, and pyrolyzing after ion exchange to obtain battery-grade lithium carbonate. This process can effectively control the impurity content of the product and obtain battery-grade or high-purity lithium carbonate products. However, its industrial-grade lithium carbonate carbonization conversion efficiency is low and the amount of carbon dioxide used is large, which does not comply with the current carbon neutrality and carbon emission policies. Summary of the invention

[0006] In view of the above problems, the present invention provides a purification process for lithium carbonate, wherein the high-sulfur salt lithium precipitation mother liquor is evaporated and concentrated in sequence, calcium and magnesium ions in the filtrate are adsorbed with a homemade chelating resin, and then a lithium precipitation reaction is carried out to obtain lithium carbonate slurry, the lithium carbonate slurry is pumped into a smart cutting sharp grinding system for cyclic shearing, and pure water is added for two-stage water washing, wherein the smart cutting sharp grinding system is used for secondary cyclic shearing in the secondary water washing process, and battery-grade lithium carbonate with a purity greater than 99.6% is obtained through the five steps, and the impurity content indicators of each are lower than the standard limit.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing battery-grade lithium carbonate comprises the following steps:

[0009] S1: decarbonizing the lithium precipitation mother liquor, and then evaporating and concentrating the lithium precipitation mother liquor after decarbonization, filtering, and obtaining a concentrated solution;

[0010] S2: preparing a chelating resin capable of removing calcium and magnesium in a high sodium sulfate environment;

[0011] S3: using a chelating resin to adsorb the concentrated solution to obtain a calcium and magnesium-removed concentrated solution;

[0012] S4: adding sodium carbonate solution to the concentrated solution to precipitate lithium to obtain lithium carbonate slurry, and subjecting the lithium carbonate slurry to a cyclic shearing process;

[0013] S5: filtering the lithium carbonate slurry after the first cycle shearing, performing two-stage water washing on the filtered lithium carbonate, and after the water washing, filtering to obtain battery-grade lithium carbonate, wherein the second cycle shearing is performed during the two-stage water washing process.

[0014] As a preferred embodiment of the present invention, in step S1, the lithium precipitation mother liquor is obtained by removing impurities, concentrating and precipitating lithium from lithium iron phosphate positive electrode powder.

[0015] As a preferred embodiment of the present invention, in step S1, the lithium content in the lithium precipitation mother liquor is 1.5-2.5 g / L, the sulfate content is 150-170 g / L, the chloride ion content is 1-2 g / L, and the calcium and magnesium ion concentrations are both 0.005-0.008 g / L.

[0016] As a preferred embodiment of the present invention, in step S1, the lithium ion concentration in the concentrated solution is 15-20 g / L.

[0017] As a preferred embodiment of the present invention, in step S2, the preparation method of the chelating resin is as follows:

[0018] Glycidyl methacrylate and N,N-dimethylformamide are stirred and mixed at a ratio of 1:(3-5) for 24-36 hours to obtain a first mixed solution, polystyrene resin and the first mixed solution are mixed at a solid-liquid ratio of 1:(5-7), ultrasonicated for 20-30 minutes, and dried to obtain PGMA@PS resin; 5-aminosalicylic acid and 2-imidazolylethylamine are dissolved in deionized water at a ratio of 1:(2-4), and the pH is adjusted to 10-12, tetrahydrofuran is added to obtain a second mixed solution, the second mixed solution and PGMA@PS resin are hydrothermally reacted at 80-90°C at a liquid-solid ratio of (4-6):1, and after the reaction is completed, it is washed with 10-30vt% ethanol solution to obtain ASA / IMEA / PGMA@PS resin, that is, a chelating resin is obtained.

[0019] As a preferred embodiment of the present invention, in step S3, the concentrations of calcium and magnesium ions in the concentrated solution are controlled below 0.001 g / L.

[0020] As a preferred embodiment of the present invention, the chelating resin is regenerated by acid and alkali solutions respectively after use, and the concentrated solution can be reused after calcium and magnesium are removed.

[0021] As a preferred solution of the present invention, step S4 includes at least one of the following technical features:

[0022] One cycle of shearing is carried out in the Zhiqie sharp grinding system for 1-3 hours, specifically 1 hour, 2 hours, or 3 hours;

[0023] The shearing temperature of one cycle is 80-90°C, specifically 80°C, 85°C, or 90°C, and the shearing rate of one cycle is 100-200m 3 / h, specifically 100, 120, 140, 160, 180, or 200m 3 / h;

[0024] The particle size of lithium carbonate after one cycle of shearing is controlled at 20 to 25 μm.

[0025] As a preferred embodiment of the present invention, in step S5,

[0026] During the two water washings, the solid-to-liquid ratio of lithium carbonate to pure water is 1:(3-4), specifically 1:3, 1:3.5, or 1:4;

[0027] During the two water washings, the temperature is maintained at 80-90° C., and both water washing processes are circulated through the Zhiqie sharp grinding system for shear cleaning for 1-3 hours.

[0028] The present invention also discloses a battery-grade lithium carbonate, which is prepared by any of the above preparation methods.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention uses lithium iron phosphate positive electrode powder to remove impurities, concentrate, and precipitate lithium, and then uses evaporation to concentrate the lithium ion concentration in the solution. Since the concentration of calcium and magnesium ions in the solution increases after concentration, traditional resins cannot remove the calcium and magnesium ion content in the solution at one time under a high sodium sulfate salt system. The present invention uses a self-made chelating resin to adsorb calcium and magnesium ions in the filtrate. The self-made chelating resin increases the chelating group for calcium and magnesium ions. Under a high sodium sulfate salt system, the chelating group shows good tolerance and has better chelating performance for calcium and magnesium ions.

[0031] (2) The present invention utilizes sodium carbonate solution and the concentrated solution after the resin removes calcium and magnesium to carry out lithium precipitation reaction. After obtaining lithium carbonate slurry, the lithium carbonate slurry is pumped into the intelligent cutting sharp grinding system for cyclic shearing to solve the problem of peritectic formed by lithium carbonate encapsulating sodium and sulfate ions during the lithium precipitation process. After the cyclic shearing, the lithium carbonate is filtered out and pure water is added for two-stage water washing. In the second-stage water washing process, the intelligent cutting sharp grinding system is used for secondary cyclic shearing. After the washing is completed, battery-grade lithium carbonate is obtained by filtration.

[0032] (3) At present, the more mature process for purifying lithium carbonate is the carbonization process. The present invention creates another method for sinking lithium from a high-sulfur salt system to obtain battery-grade lithium carbonate, which can effectively reduce the production cost for producing battery-grade lithium carbonate.

[0033] (4) The purity of the lithium carbonate obtained by the present invention is above 99.6%, and the calcium, magnesium, sodium and sulfate ions meet the standards of battery-grade lithium carbonate. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The process equipment flow chart of Example 1;

[0035] In the figure, 100-decarbonization tank, 200-evaporation system, 300-chelating resin, 400-sharpening system, 500-primary water washing tank, 600-secondary water washing tank, 700-centrifuge, 800-primary water washing centrifuge, 900-secondary water washing centrifuge. DETAILED DESCRIPTION

[0036] For high sulfate systems, the most direct way at present is to precipitate lithium after evaporation and concentration, and then purify it through carbonization to obtain a battery-grade lithium carbonate product. The present invention purifies the high-sulfur salt system to prepare battery-grade lithium carbonate, and provides another purification process, which is mainly composed of five steps: 1. After decarbonization, the high-sulfur salt lithium precipitation mother liquor is evaporated and concentrated in turn to precipitate sodium sulfate salt, and the lithium ion concentration in the solution is increased. 2. Prepare a strong chelating calcium and magnesium removal ASA / IMEA / PGMA@PS resin for removing calcium and magnesium from the high sulfate sodium salt system in the solution. 3. The concentrated solution uses a homemade chelating resin to adsorb calcium and magnesium ions in the filtrate to obtain a concentrated solution after calcium and magnesium are removed. 4. The sodium carbonate solution reacts with the concentrated solution after calcium and magnesium are removed to precipitate lithium, and after obtaining a lithium carbonate slurry, the lithium carbonate slurry is pumped into the Zhiqie sharp grinding system for cyclic shearing. 5. After the cyclic shearing, the lithium carbonate is filtered out and pure water is added for two-stage washing. In the second-stage washing process, the Zhiqie sharp grinding system is used for secondary cyclic shearing. After the washing, battery-grade lithium carbonate is obtained by filtration. The lithium carbonate obtained in this process has high purity and low equipment requirements, which effectively reduces the production cost required for lithium carbonate purification.

[0037] The present invention provides a method for preparing battery-grade lithium carbonate, specifically a method for preparing and purifying battery-grade lithium carbonate using a high-sulfate sodium salt system lithium precipitation concentrate. The process flow is as follows: Figure 1 , including the following steps:

[0038] S1: The lithium precipitation mother liquor after lithium precipitation is decarbonized in the decarbonization reactor 100, and the lithium precipitation mother liquor after decarbonization is evaporated and concentrated in the evaporation concentration system 200. The concentrated liquid after evaporation and concentration is filtered in a high sodium sulfate salt system, and a part of the sodium sulfate salt is filtered out, and the lithium ion concentration in the solution is increased at the same time.

[0039] S2: Glycidyl methacrylate and N,N-dimethylformamide were stirred and mixed at a ratio of 1:(3-5) for 24-36h, polystyrene resin and the above solution were mixed at a solid-liquid ratio of 1:(5-7), and ultrasonicated for 20-30min using an ultrasonicator. After ultrasonication, the resin was placed in a vacuum drying oven at 70°C for drying to prepare PGMA@PS resin. 5-aminosalicylic acid and 2-imidazolylethylamine were dissolved in deionized water at a ratio of 1:(2-4), and the pH was adjusted to 10-12 with NaOH solution. After tetrahydrofuran was added, the mixture was hydrothermally reacted with PGMA@PS resin at a liquid-solid ratio of (4-6):1 at 80-90°C. After the reaction, it was washed with 10-30vt% ethanol solution to prepare ASA / IMEA / PGMA@PS resin for removing calcium and magnesium ions.

[0040] S3: The concentrated solution obtained in S1 is used to adsorb calcium and magnesium ions in the filtrate by a chelating resin 300 to obtain a concentrated solution after calcium and magnesium are removed.

[0041] S4: After the sodium carbonate solution and the concentrated solution are subjected to lithium precipitation reaction to obtain lithium carbonate slurry, the lithium carbonate slurry is pumped into the intelligent cutting and sharpening system 400 for cyclic shearing.

[0042] S5: After cyclic shearing of S4, lithium carbonate is filtered out, and pure water is added to perform two-stage water washing in the primary water washing tank 500 and the secondary water washing tank 600 in sequence. During the secondary water washing process, the intelligent cutting and sharp grinding system 400 is used to perform secondary cyclic shearing for 1 to 3 hours. After the water washing is completed, battery-grade lithium carbonate is obtained by filtration.

[0043] Preferably, the lithium ion concentration in the concentrated liquid after the evaporation and concentration treatment by the evaporation and concentration system 200 in step S1 is 15-20 g / L.

[0044] Preferably, in step S2, the ASA / IMEA / PGMA@PS resin is a chelating resin 300.

[0045] Preferably, after the concentrated liquid in step S3 passes through an ion exchange resin, the concentrations of calcium and magnesium ions are controlled below 0.001 g / L.

[0046] Preferably, the chelating resin in step S3 is regenerated by acid and alkali solutions respectively after use, and the concentrated solution is reused after calcium and magnesium are removed.

[0047] Preferably, in step S4, the sodium carbonate slurry is pumped into the intelligent cutting sharp grinding system 400, maintained at a temperature of 80 to 90°C, and the temperature is adjusted to 100 to 200 m 3 / h rate of shearing through the system.

[0048] Preferably, in step S4, the smart cutting and sharp grinding system 400 is a shearing slurry crystal package equipment, which is designed to open the peritectic and solve the peritectic formed by lithium carbonate encapsulating sodium and sulfate ions during lithium precipitation.

[0049] Preferably, in step S4, the particle size of lithium carbonate after cyclic shearing is 20-25 μm, and when the system shearing reaches this particle size, the shearing is automatically stopped through the control panel.

[0050] Preferably, in step S5, during the two water washings, the solid-to-liquid ratio of lithium carbonate to pure water is 1:(3-4).

[0051] Preferably, during the two water washings in step S5, the temperature is maintained at 80-90° C., and both water washing processes are circulated through the smart cutting and sharpening system 400 for shear cleaning for 1-3 hours.

[0052] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0053] The lithium solution in the high-sulfate sodium salt system used in the present invention is a lithium precipitation mother liquor obtained after leaching, removing impurities and precipitating lithium from lithium iron phosphate positive electrode powder, with a lithium content of 2.5 g / L, and impurities mainly including sodium ions of 80 g / L, sulfate ions of 170 g / L, chloride ions of 1.5 g / L, and calcium and magnesium ion concentrations of 0.008 g / L.

[0054] The detection methods in the following embodiments: the test methods and indicators comply with YS / T 582-2013, GB / T 23853-2022, and related test methods.

[0055] Example 1

[0056] (1) Evaporation concentration

[0057] The lithium precipitation mother liquor obtained after leaching, impurity removal and lithium precipitation of lithium iron phosphate positive electrode powder is adjusted to pH 3 by adding sulfuric acid, and then adjusted to pH 7 by adding sodium hydroxide. After decarbonization, it is passed through an evaporation concentration system to concentrate the lithium concentration in the lithium precipitation mother liquor to 20g / L. Some sodium sulfate will precipitate during the concentration process. After centrifugal separation, a concentrated liquid is obtained.

[0058] (2) Preparation of ASA / IMEA / PGMA@PS resin

[0059] Glycidyl methacrylate and N,N-dimethylformamide were stirred and mixed at a ratio of 1:3 for 24 hours, polystyrene resin and the above solution were mixed at a solid-liquid ratio of 1:5, and ultrasonicated for 30 minutes using an ultrasonicator. After ultrasonication, the resin was placed in a 70°C vacuum drying oven for drying to prepare PGMA@PS resin. 5-aminosalicylic acid and 2-imidazolylethylamine were dissolved in deionized water at a ratio of 1:2, and the pH was adjusted to 11 with NaOH solution. After tetrahydrofuran was added, it was hydrothermally reacted with PGMA@PS resin at a liquid-solid ratio of 4:1 at 80°C. After the reaction, it was washed with 10vt% ethanol solution to prepare ASA / IMEA / PGMA@PS resin for removing calcium and magnesium ions.

[0060] (3) Resin removal of calcium and magnesium

[0061] The decarbonized and evaporated liquid was concentrated to 2.5m 3 / h passes through the ASA / IMEA / PGMA@PS resin system every hour. The concentration of calcium and magnesium ions is 0.008g / L before entering the resin. After entering the resin, the concentration of calcium and magnesium ions is controlled below 0.001g / L. After use, the chelating resin is regenerated with acid and alkali solutions respectively, and the concentrated solution can be reused to remove calcium and magnesium.

[0062] (4) Shear deposition of lithium

[0063] Add sodium carbonate solution into the lithium precipitation reaction tank at a flow rate of 2.5m 3 / h, add the concentrated resin solution to carry out lithium precipitation reaction, and pump the sodium carbonate slurry obtained by lithium precipitation into the Zhiqie sharp grinding system in a cycle, maintain the temperature at 80℃, and 3 The system shears the lithium carbonate slurry at a rate of / h. When the particle size of lithium carbonate in the sheared lithium carbonate slurry is 20μm, the shearing system stops automatically, and the lithium carbonate wet material is obtained by centrifugation and transferred to the next level water washing process.

[0064] (5) Two-stage shear water washing

[0065] The lithium carbonate obtained by shearing lithium precipitation is added to the washing tank, and the solid-liquid ratio of lithium carbonate to pure water is 1:4 for water washing process, and the temperature is maintained at 80℃. The two-stage water washing process is carried out according to 200m 3 The product is circulated through the Zhiqie Rui grinding system at a rate of / h for shear cleaning for 1 hour. The qualified purity products are calcined, jet milled, and iron removed to meet the standards of battery-grade lithium carbonate before being packaged and sold.

[0066] The purity of lithium carbonate obtained in Example 1 is above 99.6%, and the calcium, magnesium, sodium and sulfate ions meet the standards of battery-grade lithium carbonate. The specific components are shown in Table 1:

[0067] Table 1 Technical indicators

[0068]

[0069] Comparative Example 1

[0070] Compared with Example 1, step 3) of removing calcium and magnesium by resin is not performed.

[0071] Since the obtained lithium carbonate is not subjected to resin to remove calcium and magnesium, metal carbonates are formed with sodium carbonate during the lithium precipitation process and remain in the product. Therefore, the calcium and magnesium contents in the product exceed the battery-grade lithium carbonate standard. The specific composition is shown in Table 2.

[0072] Table 2 Technical Specifications

[0073]

[0074] Comparative Example 2

[0075] Compared with Example 1, in step 3), unmodified resin is used to remove calcium and magnesium, that is, polystyrene resin is directly used.

[0076] The concentrate in the high-sulfur salt system contains a large amount of sodium ions and sulfate ions, and the concentration of calcium and magnesium ions in the concentrated solution is relatively high. The unmodified resin does not have enough chelating sites to chelate the calcium and magnesium ions in the concentrate. In addition, in the high-salt system, the tolerance of the chelating site groups in the unmodified resin is reduced. Therefore, after using the unmodified resin to remove calcium and magnesium, the calcium and magnesium ions in the product do not meet the battery-grade lithium carbonate standard. The specific composition is shown in Table 3.

[0077] Table 3 Technical indicators

[0078]

[0079]

[0080] Comparative Example 3

[0081] Compared with Example 1, in step 4 and step 5), the smart cutting sharp grinding system is not used for cyclic shearing during lithium precipitation and water washing.

[0082] The concentrated solution in the high-sulfur salt system contains a large amount of sodium ions and sulfate ions. During the lithium precipitation process, lithium carbonate will show phenomena such as crystal aggregation, solution inclusion, and crystal defect embedding, causing the lithium carbonate to be wrapped with sodium and sulfate ions. Therefore, the sodium ion and sulfate content in the product exceeds the battery-grade lithium carbonate standard. The specific composition is shown in Table 4.

[0083] Table 4 Technical Specifications

[0084]

[0085]

[0086] Comparative Example 4

[0087] Compared with Example 1, the two-stage water washing process in step 5) does not use the smart cutting and sharpening system for cyclic shearing.

[0088] The use of the Zhiqie sharp grinding system for cyclic shearing in the lithium precipitation process can effectively reduce the sodium ion concentration in the product. However, since lithium is precipitated using a high-sulfur salt system lithium precipitation concentrate, the sulfate concentration is high. It is difficult to achieve battery-grade lithium carbonate standards using only cyclic shearing of lithium precipitation. The specific composition is shown in Table 5.

[0089] Table 5 Technical Specifications

[0090]

[0091] Comparative Example 5

[0092] Compared with Example 1), the lithium carbonate in this comparative example is purified by carbonization method, and the specific steps are as follows:

[0093] (1) Evaporation concentration

[0094] The lithium precipitation mother liquor obtained after leaching, impurity removal and lithium precipitation of lithium iron phosphate positive electrode powder is adjusted to pH 3 by adding sulfuric acid, and then adjusted to pH 7 by adding sodium hydroxide. After decarbonization, it is passed through an evaporation concentration system to concentrate the lithium concentration in the lithium precipitation mother liquor to 20g / L. Some sodium sulfate will precipitate during the concentration process. After centrifugal separation, a concentrated liquid is obtained.

[0095] (2) Resin for removing calcium and magnesium

[0096] The decarbonized and evaporated liquid was concentrated to 2.5m 3 / h passes through the ASA / IMEA / PGMA@PS resin system every hour. The concentration of calcium and magnesium ions is 0.008g / L before entering the resin. After entering the resin, the concentration of calcium and magnesium ions is controlled below 0.001g / L. After use, the resin is regenerated with acid and alkali solutions respectively, and the concentrated liquid can be reused after calcium and magnesium are removed.

[0097] (3) Lithium deposition

[0098] Add sodium carbonate solution into the lithium precipitation reaction tank at a flow rate of 2m 3 / h, the concentrated liquid from the resin is added to carry out lithium precipitation reaction, and the sodium carbonate slurry obtained by lithium precipitation is centrifuged to obtain lithium carbonate wet material, which is transferred to the next carbonization process.

[0099] (4) Carbonization

[0100] Pure water and lithium carbonate are slurried at a liquid-to-solid ratio of 40:1. Carbon dioxide is added to the lithium carbonate slurry at a temperature of 25°C. The reaction is terminated when the pH of the slurry reaches 7. The lithium bicarbonate solution obtained by the carbonization reaction enters the next stage of pyrolysis.

[0101] (5) Pyrolysis

[0102] The obtained liquid is precisely filtered, and the filtrate is continuously stirred at 80°C to evaporate and crystallize to obtain lithium carbonate precipitate. The carbon dioxide is decomposed and circulated into the carbonization system. The lithium carbonate is dried to obtain a battery-grade product.

[0103] Carbonization is the most mature lithium carbonate purification technology and can effectively reduce soluble impurities such as sodium, potassium, chlorine, and sulfate. Considering the high cost of carbonization, carbonization technology is not the most economical and practical purification method. After carbonization purification, the specific composition of lithium carbonate is shown in Table 6.

[0104] Table 6 Technical Specifications

[0105]

[0106] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.

Claims

1. A method for preparing battery-grade lithium carbonate, characterized in that: The following steps are involved: S1: decarbonizing the lithium precipitation mother liquor, and then evaporating and concentrating the lithium precipitation mother liquor after decarbonization, filtering, and obtaining a concentrated solution; S2: preparing a chelating resin capable of removing calcium and magnesium in a high sodium sulfate environment; S3: using a chelating resin to adsorb the concentrated solution to obtain a calcium and magnesium-removed concentrated solution; S4: adding sodium carbonate solution to the concentrated solution to precipitate lithium to obtain lithium carbonate slurry, and subjecting the lithium carbonate slurry to a cyclic shearing process; S5: filtering the lithium carbonate slurry after the first cycle shearing, performing two-stage water washing on the filtered lithium carbonate, and after the water washing, filtering to obtain battery-grade lithium carbonate, wherein the second cycle shearing is performed during the two-stage water washing process.

2. The preparation method according to claim 1, characterized in that: In step S1, the lithium precipitation mother liquor is obtained after the lithium iron phosphate positive electrode powder is removed from impurities, concentrated, and lithium is precipitated.

3. The preparation method according to claim 1, characterized in that: In step S1, The lithium content in the lithium precipitation mother liquor is 1.5-2.5 g / L, the sulfate content is 150-170 g / L, the chloride ion content is 1-2 g / L, and the calcium and magnesium ion concentrations are both 0.005-0.008 g / L.

4. The preparation method according to claim 1, characterized in that: In step S1, the lithium ion concentration in the concentrated solution is 15-20 g / L.

5. The preparation method according to claim 1, characterized in that: In step S2, the preparation method of the chelating resin is as follows: Glycidyl methacrylate and N,N-dimethylformamide are stirred and mixed at a ratio of 1:(3-5) for 24-36 hours to obtain a first mixed solution, polystyrene resin and the first mixed solution are mixed at a solid-liquid ratio of 1:(5-7), ultrasonicated for 20-30 minutes, and dried to obtain PGMA@PS resin; 5-aminosalicylic acid and 2-imidazolylethylamine are dissolved in deionized water at a ratio of 1:(2-4), and the pH is adjusted to 10-12, tetrahydrofuran is added to obtain a second mixed solution, the second mixed solution and PGMA@PS resin are hydrothermally reacted at 80-90°C at a liquid-solid ratio of (4-6):1, and after the reaction is completed, it is washed with 10-30vt% ethanol solution to obtain ASA / IMEA / PGMA@PS resin, that is, a chelating resin is obtained.

6. The preparation method according to claim 1, characterized in that: In step S3, the concentrations of calcium and magnesium ions in the concentrated solution are controlled below 0.001 g / L.

7. The preparation method according to claim 1, characterized in that: After use, the chelating resin is regenerated by acid and alkali solutions respectively, and can be reused to remove calcium and magnesium from the concentrated liquid.

8. The preparation method according to claim 1, characterized in that: In step S4, at least one of the following technical features is included: One cycle of shearing takes 1-3 hours in the Zhiqie sharp grinding system; The shear temperature of one cycle is 80~90℃, and the shear rate of one cycle is 100~200m 3 / h; The particle size of lithium carbonate after one cycle of shearing is controlled at 20 to 25 μm.

9. The preparation method according to claim 1, characterized in that: In step S5, During the two water washings, the solid-to-liquid ratio of lithium carbonate to pure water is 1:(3-4); During the two water washings, the temperature is maintained at 80-90° C., and both water washing processes are circulated through the Zhiqie sharp grinding system for shear cleaning for 1-3 hours.

10. A battery-grade lithium carbonate, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Method and equipment for preparing battery-grade lithium carbonate by optimizing low-purity lithium carbonate

    CN121063559A

  • A system and method for removing aluminum

    CN123005106A